Concurrent Spectrophotometric Assay of Pseudoephedrine and Cetrizine from Combination Tablets - Sahu, L.K.; Gupta, J.K.; Si, S.; Patro, S.K. (Asian Journal of Chemistry, 2016)
Two simple methods based on simultaneous equations (Vierdot’s Method) and absorbance difference with correlation regression equations, respectively for simultaneous estimation of pseudoephedrine and cetrizine in multicomponent formulations have been presented. Proper selection of wavelengths with utilization of correlative regression equations and simultaneous equations eliminates complex interference raised in estimation of one drug by another. The results of analysis have been validated statistically at a 95 per cent confidence level with Student's t-test and by recovery studies.